Explaining South Asia's Development Success : The Role of Good Policies - Ahmed, Sadiq (Washington, DC: World Bank, 2012)
South Asia has performed well over the past 25 years in reducing poverty, improving human development and increasing growth, but faster progress with poverty reduction will require a higher rate of growth. This book shows that the development performance is not a puzzle but largely explained by good policies. Countries in the region have maintained good macroeconomic environments, opened up their economies to greater domestic and international competition, and reduced the role of corrupt and inefficient public enterprises.